Hydroallantois in a Gir Cow: A Case Report - Bharai, Munja J.; Dodiya, Vivek A. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Hydroallantois is a pathological condition characterized by excess accumulation of allantoic fluid in the allanatois  during fetal development. Usually, maternal factors are  involved, where rapid and abnormal distension of the  abdomen occurs (Drivers Peek, 2008). If the case is not  diagnosed and treated early and the animal cannot rise,  the prognosis is poor. In dairy cattle, hydroallantois is  more common in the last phase of the third trimester and  less so in buffaloes and heifers (Kumar et al., 1988; Srinivas  and Sreenu, 2006). The physiopathology of hydroallantois  reduces placental vascularization resulting in metabolic  changes in the placental tissue and fetal membranes, thereby  accumulating fetal fluids (Kapadiya et al., 2018).
Keywords: Hydroallantois; Gir Cow